Simultaneous Determining the Total Elements in Purple Pepper Fruit by ICP-MS - Sun1, Pengfei; Rui2, Yukui (Asian Journal of Chemistry, 2014)
Purple pepper (Capsicum annuum L.) is a rare pepper germplasm resources, but trace elements and heavy metals in the purple pepper was not reported. Five macroelements, six trace elements, four rare earth elements and eleven heavy metals were determined in purple pepper. The results showed that descending order of macroelements is P > Ca > Mg > Na > Al; three kinds of trace elements Fe, Zn and Mn were much higher than other three elements Mo, Li and Co; rare earth elements were very low in in fruits of purple pepper; only Cu (277.80 ng/g) and Ti (130.79 ng/g) were higher than 100 ng/g, all the heavy metals were meet to the National hygiene standards.